2015
DOI: 10.1115/1.4030316
|View full text |Cite
|
Sign up to set email alerts
|

Offshore Wind Foundation Design: Some Key Issues

Abstract: Despite the growth of the offshore wind industry, there are currently doubts relating to the design of wind facilities in the sea. This paper expounds current, already identified structural uncertainties: problems for soil characterization and transition piece (TP) design. This document also introduces new doubts or issues to be researched in the near future in this field (wave theory, scour process, wave load actions, scale difficulty, etc.), not as yet identified due to the scarce experience in the offshore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…For natural factors, wind energy potential, including , and V, are considered to be the most important indicators in almost every study [1][2][3][4][5]. Terrain and littoral factors, including , , ℎ, and , are also crucial to the engineering construction of OWFs [25].…”
Section: Indicator Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…For natural factors, wind energy potential, including , and V, are considered to be the most important indicators in almost every study [1][2][3][4][5]. Terrain and littoral factors, including , , ℎ, and , are also crucial to the engineering construction of OWFs [25].…”
Section: Indicator Analysismentioning
confidence: 99%
“…The site selection for wind farms is a process of finding locations with rich wind energy resources and great economic benefit through evaluation of all kinds of conditions, such as meteorology, geography, society, and economy. According to the different scale of siting areas, it is divided into macrosite selection (the regional scale) and microsite selection (the scale of the farm) [3]. What we study is macrositing in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…Off-shore wind farms have a crescent importance in the world and some experiences with caissons have been developed [48][49][50]. Since the foundation represents a big amount of the investment (35%) [51] and considering that it is a very important element in the structure, that opens up another field for caisson technology.…”
Section: Evolution Of the Construction In The 20th Centurymentioning
confidence: 99%
“…Therefore, the choice of support structures and their production, transportation, and installation methods is particularly important. Support structures account for a large part-as much as 20-40%-of the total capital costs of offshore wind farms [13][14][15][16]. Indeed, it has been reported that optimization of the support structure presents the largest cost-reduction potential regarding investment costs [17].…”
Section: Introductionmentioning
confidence: 99%